(untitled) (Iraqi Journal of Medical Sciences, 2016)
Background:Polyvinyl chloride (PVC) is used in production and manufacturing of many essential tools for example plastic pipes, fabric, cables, decorative products etc.). Its production is impossible without the use of vinyl chloride monomer (VCM), which can cause liver damage in long-term. Objective:To assess the effects of mild to moderate long term exposure to VCM on liver and to assess the importance of liver enzyme measurements as screening tools. Methods:In this study, measurement of serum levels of liver enzymes of 64 exposed workers and 61control workers was carried out starting from the first of October 2010 till the end of January 2011. All of the studied cases were worked in a poly vinyl chloride (PVC) production unit in three polyvinyl chloride factories and considered as target population for detection of any possible industrial vinyl chloride associated liver enzymes changes. The controls were randomly selected from office personnel of the same factories. Biochemical paramedics and a questionnaire method were used for analysis and in both groups. Results:Both groups have a similar age structure. Statistical difference was noted between the alanine aminotransferase (ALT) and gamma-glutamyl transferase (GGT) mean values for both the exposed and non-exposed groups. The mean values for alpha-2-globulin and gamma-globulin in both exposed and non exposed groups of serum electrophoresis were statistically significant. The relative risk for the exposed workers was higher than that one for all other variables. It was the highest and most significant for gamma-globulin abnormal values associated among the exposed group followed by the relative risk of alpha-2- globulin. Conclusion:Liver function tests with serum protein electrophoresis are useful to detect hepatic damage among workers exposed to polyvinylchloride. Key words:Liver Enzymes, Workers, Protein Electrophoresis, Vinyl Chloride